Increased serum estrogenic bioactivity in girls with premature thelarche: a marker of environmental pollutant exposure?. (August 2013) - Paris, Françoise; Gaspari, Laura; Servant, Nadège; Philibert, Pascal; Sultan, Charles
Abstract The aim of the work was to investigate the pathophysiology of isolated premature thelarche (IPT) by determining the impact of pre/postnatal exposure to endocrine disrupting chemicals (EDCs) through evaluation of total serum estrogenic bioactivity (EBA). The pathophysiology remains elusive, although recent investigations suggested the role of EDCs in premature female breast development. We investigated 15 girls with IPT. Plasma estradiol, follicle-stimulating hormone, and luteinizing hormone were measured in basal state and after gonadotropin-releasing hormone testing; bone age and uterine length were also assessed for all patients. Total EBA of patient serum was analyzed with an ultrasensitive bioassay that we previously developed and compared with that of 18 age-matched control girls. Parents were interviewed about their environmental/occupational exposure to EDCs during the patient's prenatal/postnatal life. Nine families reported parental occupational/environmental EDCs exposure during prenatal/postnatal patient life; the mean total EBA found in these 9 IPT girls was significantly elevated (12.31 ± 6.64 pg/mL) in comparison with that of the 6 patients without exposure (2.53 ± 0.73 pg/mL) and the 18 age-matched controls (3.53 ± 2.23 pg/mL; p < 0.01). The significant increase in total EBA in these 9 girls with IPT suggests that premature female breast development may be related in some cases to higher pre/postnatal contamination by EDCs.